Upgrading videography knowledge and skills in making Canva-based learning videos for elementary school teachers - Sri Hapsari Wijayanti; Alfonso Harrison; Yohanna Claudia Dhian; Theodora Jessica; Margaretha Theresia (University of Merdeka Malang, 2023)
Utilizing videos as a learning tool is known to enhance motivation. To create more professional learning videos, understanding videography techniques is crucial. The Canva application, widely popular today, aids education by facilitating the design of engaging learning videos. Unfortunately, teachers in the Teacher Working Group (KKG) Cluster 10, Cisauk District, lack proficiency in using Canva, particularly in crafting learning videos. The community service aims to enhance the knowledge and skills of 28 participants from 9 public elementary schools and 1 private elementary school in Cisauk District, focusing on videography techniques and Canva application operation. Scheduled from September to October 2023 at SDN Suradita, the activity involves preparation, training, assignments, and concludes with monitoring and evaluation. Evaluation results indicate a 30% increase in teachers' knowledge and a 4.6% boost in insight into videography and Canva. Similarly, teachers' proficiency in crafting learning videos with Canva improves. However, limited activity time prevents teachers from applying videography techniques with complete camera devices. The next step involves testing Canva-produced learning videos to gauge their impact on student learning outcomes and motivation.